Centralization and Reduced Financial Resources: A Worrying Picture for Hungarian Municipalities - Judit Siket (Central European Public Administration Review)
The article provides an overview of governmental regulations affecting the operation and economic situation of local self-governments in Hungary during the pandemic crisis. The research covers the period from the declaration of the state of emergency in March 2020 until the end of the year. The study aims to explore the implementation of the European Charter of Local Self-Government’s special provisions related to local democracy concerns in times of crisis. The article analyses the relationship between the pandemic and governmental measures that affected the economic position of local self-governments. It does not provide an objective assessment, but rather presents and analyses the relevant resources. The article is primarily based on the review of the legal framework and the relevant Constitutional Court’s decisions. The analysis demonstrates that the Constitutional Court did not or only partially defended the legal interests of local self-governments. The governmental measures ‘stood the test of constitutionality’. The study confirms the initial assumption that the excessive centralization process was significantly reinforced, while the position of local self-governments in the  state organs system weakened. However, some measures cause concern as they highlight deeper problems in the Hungarian legal system, irrespective of the pandemic.